Portal for research in electrophysiology - Data integration with neuroscience information framework - Bruha, Petr; Moucek, Roman (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
There is a problem with global search and data sharing. Our research group developed the EEG/ERP (electroencephalography, event-related potentials) portal; a system for storage and management of EEG/ERP resources - data, metadata, tools and materials related to EEG/ERP experiments. The EEG/ERP portal and existing solutions of data integration are presented. Authors registered the EEG/ERP portal as a source of neuroscience data and metadata within the world known project - Neuroscience Information Framework (NIF). Developed web services for harvesting EEG/ERP scenarios and experiments within NIF are presented.